Caractérisation Physiologique Et Évaluation Du Comportement Germinatif De Semences De Rottboellia Cochinchinensis, Euphorbia Heterophylla, Et Porophyllum Ruderale, Trois Adventices Des Rizières De Côte d’Ivoire - Yao, Akoua Clémentine; Ipou, Ipou Joseph; Bomisso, Edson Lézin; Angaman, Djédoux Maxime; Koné, Mamidou Witabouna (European Scientific Journal, ESJ, 2017)
Weeds are the most important biological constraint reducing rice production. This study was conducted to know the physiological characteristics and the germinative behavior of the seeds of Rottboellia cochinchinensis, Euphorbia heterophylla and Porophyllum ruderale, three major weeds of rice field in Côte d’Ivoire. Seed characteristics were determined according to ISTA’s standards. These three weeds had orthodox seeds with low moisture content (< 15%). These weeds raise better when they were sown on the surface (0-0.5 cm) or slightly buried in the ground. E. heterophylla and P. ruderale germinated well when their seeding density is high (150 seeds/Petri dish). For R. cochinchinensis, when the seedling density is low (25 seeds/Petri dish). The germination was maximum after five to nine days.